2017
DOI: 10.1080/14786419.2016.1274887
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprinting of strong spermatogenesis steroidal saponins in male flowers ofPhoenix dactylifera(Date Palm) by LC-ESI-MS

Abstract: A fingerprint of steroid saponins, the major constituent in 80% methanolic fraction from the male flowers of Phoenix dactylifera has been established. Under ESI-MS/MS conditions, the fragmentation patterns of [M - H] ions exclusively displayed signals corresponding to the cleavage of the glycosidic bonds, thus allowing a rapid identification of 21 steroidal saponins. Moreover, two unique among them conjugated with histidine were detected by LC-ESI (-)-MS and DFT and were given tentative names of 3-o-histidine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…To date, little phytochemical studies were reported for P. dactylifera male flowers [18]. The present work is focused on the analysis of the phenolic constituents of P. dactylifera male flowers as a novel rich source of phenolic acids, flavonoids and proanthocyanidins.…”
Section: Introductionmentioning
confidence: 99%
“…To date, little phytochemical studies were reported for P. dactylifera male flowers [18]. The present work is focused on the analysis of the phenolic constituents of P. dactylifera male flowers as a novel rich source of phenolic acids, flavonoids and proanthocyanidins.…”
Section: Introductionmentioning
confidence: 99%
“…BLASTP analysis against the Nr database in NCBI (National Center for Biotechnology Information) identified significant CYP90G6 homologs (>80% identity) from several monocot species including Dioscorea cayenensis , Phoenix dactylifera , Asparagus officinalis , and P. polyphylla . Indeed, these species are all known to produce diosgenin or diosgenin‐related compounds (Christ et al., 2019; Hamed et al., 2017; Sautour et al., 2004; Yi et al., 2019). No significant homologs (>60% identity) were found by tBLASTN search against our previously established T. foenum‐graecum transcriptome (Zhou et al., 2019) using either Dz CYP90G6 or Dz CYP90B71 as a query protein.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the decreased TAC levels in the seminal plasma can be one of the causes of infertility. Hamed et al showed a positive relationship between sperm parameters and TAC capacity in seminal plasma (Hamed et al, 2017). In our study, decreased TAC levels in the CP group and its normal level in the SP group indicates the antioxidant effect of SP.…”
Section: Discussionmentioning
confidence: 99%